Microstructure of ceramics TiO2 obtained by protein consolidation - Santana, Jerusa Góes Aragão; de Campos, Elson; Lucena, Emerson Ferreira; Mota, Rogério Pinto [UNESP] (Trans Tech Publications, 2012)
Porous ceramics can be produced by adding starch (corn, potato) and protein (animal or vegetable) to raw material as pore forming element. In this study, titanium dioxide ceramics were formed by vegetable protein consolidation. Soybean was chosen as the binding agent and pore forming. The samples, which were produced in cylindrical shape, had the following processing: material mixture, gelling, drying, pre-sintering and sintering. Heated platinum microscopy were performed by using suspensions with different compositions in order to verify protein gelling capacity and better know the temperature in which this process occurs. The samples were characterized by apparent porosity and roughness measurement. Besides, imaging by light microscopy was also performed in order to determine the sample morphology and porosity. © (2012) Trans Tech Publications, Switzerland.
Keywords: Ceramic; Forming; Microscopic analyses; Porous; Protein; Apparent porosity; Binding agent; Cylindrical shapes; Material mixture; Microscopic analysis; Pore forming; Porous ceramics; Sample morphology; TiO; Vegetable protein; Ceramic materials; Gelation; Platinum; Sintering; Titanium dioxide; Vegetables; Proteins